Employment, Unemployment and Demand Shifts in Local Labor Markets - Holzer, Harry J. (The Review of Economics and Statistics, 1991)
This paper analyzes the effects of demand shifts within and between local labor markets on unemployment and employment levels and changes observed in those markets.